Strategi Inovasi Marketing Lembaga Pendidikan Islam Menghadapi Revolusi Industri 5.0 dengan Menggunakan SWOT Analysis (Studi Kasus KB-TK-SD IT AL Mubarokah, Rancaekek, Bandung) - Fauziah, Isma; Djatmiko, Budi (LPPM Institut Pendidikan Nusantara Global, 2024)
The research employs a qualitative method with a descriptive approach, analyzing data inductively without hypotheses. Data were obtained through in-depth observations of marketing strategies, and analysis was conducted to illustrate how these strategies can be improved. The findings suggest that to maintain and enhance quality, KB-TK-SD IT Al-Mubarokah needs to strengthen its marketing strategies and adapt to digital transformation and societal needs. KB-TK-SD IT Al-Mubarokah, a privately accredited primary school located in Bandung, West Java, uses SWOT analysis to evaluate its marketing strategies. The analysis reveals that the school’s key strengths lie in product quality and optimal digital marketing, while weaknesses include inconsistent digital services and conventional sales methods. Opportunities for growth involve leveraging digital technology and e-commerce platforms, while threats include intense competition and the need for effective communication. The proposed strategies involve leveraging strengths to exploit opportunities, addressing weaknesses through digitalization, and optimizing responses to competitive threats. By implementing these strategies, KB-TK-SD IT Al-Mubarokah aims to strengthen its competitive position and attract more students.